Effects of reduced PiO2 on training responses of elite female cyclists - Brosnan, M. J.; Martin, D. T.; Hahn, A. G.; Gore, C. J.; Hawley, J. A. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Altitude training is frequently used by competitive athletes in the belief that it increases the training stimulus and amplifies the effect of sea-level training. On the other hand, the hypoxia associated with exercise at altitude could, potentially, reduce the intensity at which athletes' train and therefore compromise adaptations to training. In this study we examined this possibility in 8 members of the Australian National Women`s Road Cycling Squad (Mean±SD: 21± 3.7 yrs, 59.61± 3.9 kg and VO2peak 3.64± 0.25 L.min-1) who completed two interval training sessions at 600 m (NORM) and 2100 m (HYPOX) simulated altitude using a repeated measures cross-over design. Cyclists performed two training sessions breathing atmospheric air (20.93% O2) and two sessions breathing hypoxic air (17% O2 ~2100m simulated altitude). Threshold interval training (3x10 min, AT) was performed on days 1 and 5 and repeat sprint intervals were performed (3x6 x 15 sec, RST) on days 3 and 7. During all interval training sessions power output (W), oxygen saturation via pulse oximetry (%SpO2), heart rate (HR), rating of perceived exertion (RPE), blood lactate (HLA), pH and bicarbonate (HCO3) were monitored. Data were analyzed using 2-way ANOVAs with repeated measures and Newman-Keuls post-hoc tests. Power output was significantly (P<.05) lower in the first interval of AT under HYPOX (226±17 W) than NORM (244±18 W), which persisted for the subsequent 2 intervals. Power output during the first set of intervals during RST was significantly lower at simulated altitude (HYPOX=459±31 W, NORM=477±52 W). A similar, significant reduction in power was observed for the second and third set of RST. %SpO2 was lower at altitude during AT for the first interval (NORM=95.4±1.5% vs. HYPOX=92.9±2.9%, P<.05) and for the subsequent two intervals. In both AT and RST HLA, HR and RPE were not significantly different between treatments (NORM vs. HYPOX). These data document that in elite female cyclists' interval training intensity is compromised at moderate altitude supporting the live high, train low model of altitude training. At simulated 2100m altitude female cyclists perform interval training at HRs and RPEs similar to those achieved at 600 m.